The Journey of Ibn al-ʿAssāl’s Introduction to the Four Holy Gospels and the Ten Canons from Cairo to Ethiopia: New Codicological Evidence - Monier, Mina (The journal of Eastern Christian studies, 2025)
Al‑Asʿad ibn al‑ʿAssāl (thirteenth century), a member of the intellectually and politically influential Coptic family Awlād al‑ʿAssāl, was renowned for his widely copied Arabic translation of the Gospels. He prefaced that translation with a comprehensive Introduction to the Four Holy Gospels and the Ten Canons. The Introduction preserves rich historical data that remain largely absent from New Testament scholarship. It also sheds light on apostolic traditions and on the use of the Eusebian canons to regulate the copying and interpretation of the text. Drawing on previously unstudied manuscripts, this article offers fresh evidence for the composition, reception, and transmission of the Introduction in Egypt, Ethiopia and Eritrea. We demonstrate that the text circulated independently, serving as a preface to other Arabic translations of the Gospels and to the Arabic Diatessaron. By comparing it with an Ethiopic Gospel introduction, we show that al‑Asʿad’s work is that text’s ultimate source, edited and translated through the efforts of the Coptic bishop Buṭrus ibn al-Khabbāz.